A study on the effect of anaerobic threshold kicking in the flume for juvenile swimmers - Shan, S.; Honghui, Y. (XIVth International Symposium on Biomechanics and Medicine in Swimming Proceedings, 2023)
INTRODUCTION Using Shanghai Swimming Flume System, this paper analyzes the effect of anaerobic threshold kicking of young swimmers in the flume, expands the flume training program of special kicking ability, improves the athletes' kicking ability. RESEARCH OBJECT AND EXPERIMENTAL SCHEME 12 male college swimmers (age 12.54±1.52yr; height 165.80±5.64cm; weight 53.14±5.49kg) participated in this study. They were randomly divided into two groups (A&B).They were given kicking training for 12 weeks.Group A arranged anaerobic threshold speed kick twice a week, the total amount of anaerobic threshold leg exercise in 1000-1200 meters. Group B used routine kick training methods. RESULTS 1. Analysis of anaerobic threshold strength kicking: anaerobic threshold kicking exercises play a very good role in coordination with the swim. It can help improve the players' ability to maintain a certain speed continuously. On the other hand, the lactic acid of anaerobic threshold kicking is not too high, which is conducive to the continuous and effective training of the players. 2. Analysis of kicking effect of anaerobic threshold speed in flume: arrange athletes in the flume kicking training, get a better effect, mainly because the flow rate in the water can enhance the stimulation of the athletes lower limb receptors, at the same time notice the position of the athletes' limbs in the water, better perception of muscle force size. DISCUSSION The anaerobic threshold strength of the kicking is helpful to improve the kicking training, arrange athletes to perform the kicking training in the flume, so that the body can get the maximum kicking effect, kicking performance has been significantly improved.